KEKERASAN SUAMI TERHADAP ISTRI DALAM PERSPEKTIF AL-QUR’AN DAN HADIST - Sylvia Kurnia Ritonga (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2022)
The issue of domestic violence is not a small issue that only occurs in families who do not have education but also occurs in educated families. The existence of an order to beat the wife when she is against her husband (nusyuz) is the entrance to violence against women in a household. This research is a literature study with a qualitative descriptive type, namely describing domestic violence according to the Qur'an and Hadith. Data were collected using document study techniques on related literature and analyzed using content analysis techniques. The results of this study indicate that the husband's violence against his wife in the household in a review of the Qur'an and hadith is the potential of the husband's ability to beat his wife for educational purposes after advising and separating beds. In fact, this stage is rarely carried out. There are various forms of sexual violence, namely physical, psychological, sexual and economic neglect. Al-Qur'an and hadith there is no verse that allows violence in a household even though there is an order to beat the wife when nusyuz except for educational purposes. Based on the analysis above, it can be concluded that Allah SWT and the Prophet did not allow violence to occur in the household.